Snake eyes - Palma, Brian De ([United States] : Touchestone Pictures, 2000)
A flamboyant Atlantic City police detective goes to watch a heavyweight championship fight and cash in on the hectic betting. Suddenly, gunfire cuts down a ringside government official and Santoro has 14,000 suspects. The clues all lead to a shattering truth Santoro does not want to believe
Editor, Bill Pankow ; executive producer, Lou Stroller ; screenplay, david Koepp
Cast: Nicholas Cage, Gary Sinise, John Heard
VCD format
Keywords: Suspense in motion pictures; Police films